W5Si3-WSi2 / WC composite material and spark plasma sintering preparation method thereof

Through the discharge plasma sintering process under high temperature and high heat pressing conditions, the problem of complex and cost of preparation of W5Si3-WSi2/WC composite materials in the prior art is solved, and the sintering effect with high density and excellent mechanical properties is achieved, and it is suitable for industrial production.

CN119530629APending Publication Date: 2025-02-28XI'AN PETROLEUM UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411724144.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-28

Smart Images

  • Figure CN119530629A_ABST
    Figure CN119530629A_ABST
Patent Text Reader

Abstract

The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight: a W5Si3 intermetallic compound and a WSi2 intermetallic compound are used as reinforcing and toughening phases; wC is used as a matrix; al2O3 powder; y2O3 powder; a phenolic resin binder; the spark plasma sintering preparation method comprises the following steps: step 1, preparing W-Si intermetallic compound powder A; secondly, the W-Si intermetallic compound powder A is subjected to heat treatment, and then W5Si3 intermetallic compound powder is obtained; step 3, preparing W-Si intermetallic compound powder B; 4, the W-Si intermetallic compound powder B is subjected to a heat treatment process, and WSi2 intermetallic compound powder is obtained; fifthly, W5Si3-WSi2 / WC composite powder is prepared; step 6, preparing a W5Si3-WSi2 / WC composite powder prefabricated blank wafer sample; step 7, putting the W5Si3-WSi2 / WC composite powder prefabricated blank wafer sample into a discharge plasma sintering furnace, and carrying out vacuum discharge plasma sintering on the W5Si3-WSi2 / WC composite powder prefabricated blank wafer sample; the W5Si3-WSi2 / WC composite material has the advantages of high preparation efficiency and simple process, and the W5Si3-WSi2 / WC composite material has high density and high mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and specifically relates to a W5Si3-WSi2 / WC composite material and a spark plasma sintering preparation method thereof. Background Art

[0002] W5Si3 (pentatungsten trisilicide) is a chemical substance with the chemical formula W5Si3 and a molecular weight of 1003.77. W5Si3 has a tetragonal crystal structure, a melting point of 2320°C, and decomposes at about 1450°C. In air, W5Si3 begins to oxidize at 500°C-700°C and can be dissolved in a mixed acid of HNO3 and HF. W5Si3 can be prepared by laser cladding technology. Laser cladding technology is an advanced surface modification technology that can prepare a cladding layer on the surface of the substrate that is metallurgically bonded with it and has excellent properties such as wear resistance, corrosion resistance, and high-temperature oxidation resistance. Transition metal W silicides (such as W5Si3 and WSi2) have high melting points, high-temperature strength, and potential low-temperature plastic deformation capabilities, but their high room temperature brittleness limits their application in industry. W5Si3 is also used in composite materials. For example, SiC / W layered composite materials are made of SiC ceramic sheets as the substrate layer and metal W as the interlayer by hot pressing and sintering. X-ray diffraction analysis shows that W in the interlayer reacts with SiC to generate W5Si3 and WC. The interlayer consists of granular crystals (W5Si3) and lamellar crystals (WC), forming a secondary layered structure. W5Si3 belongs to transition metal silicides. Such compounds usually have high melting points and high-temperature strength, but their high room-temperature brittleness limits their use in certain industrial applications. By combining with other materials such as Ni-based coatings, their toughness and strength can be improved to better meet industrial needs. Due to its high melting point and high-temperature strength, W5Si3 is widely used in aerospace, automotive, machinery, and chemical industries, especially in environments that require wear resistance, corrosion resistance, and high-temperature oxidation resistance. W5Si3 can be prepared by the reaction of tungsten and silicon. The chemical equation of the preparation process is 5W+3Si=W5Si3. The preparation process is as follows: take tungsten powder and silicon powder and mix them evenly in a molar ratio of 5:3. Put the tungsten silicon mixed powder into a sealed ball mill, draw a certain pressure of vacuum and fill it with argon, and ball mill for a period of time. The ball milled powder is left to stand in an argon atmosphere at room temperature for a period of time. The powder after standing in the argon atmosphere is heated within a certain range for a period of time to protect the atmosphere, or annealed in a vacuum at a certain pressure to obtain tungsten trisilicide pentasilicide powder. Transition metal W silicides (such as W5Si3 and WSi2) have high melting points, high high temperature strength and potential low temperature plastic deformation ability. However, as an intermetallic compound, W silicide has high room temperature brittleness, and its industrial application as friction and wear parts is also greatly limited. At present, there are many methods to improve the toughness of metal silicide coatings. The method of combining the high plasticity and toughness of Ni-based coatings with the high strength of silicides has achieved remarkable results. Tungsten-silicon binary system compounds belong to refractory metal silicides and are one of the typical representatives of metal silicides. Refractory metal silicides have unique physical, mechanical and chemical properties, such as high melting point, high strength, strong oxidation resistance and deformation resistance that increases with temperature, and have always been the focus of academic research.Among these refractory metal silicides, the tungsten-silicon binary system formed by the metal element tungsten with the highest melting point mainly includes WSi2 and W5Si3. Among them, W5Si3 has three stable phase structures, while WSi2 has two stable phase structures. The melting point of W5Si3 can be as high as 2320℃, and it has superconductivity and outstanding wear resistance, and has made great breakthroughs in the field of high-temperature performance materials and compound coatings. WSi2 material devices can be scaled down, have the characteristics of low resistivity, high stability, and good lubricity, can increase the operating speed of circuits, reduce noise, and improve the performance of integrated circuits, and have made important achievements in today's semiconductor integrated circuits. Especially in terms of process compatibility with silicon integrated circuits, WSi2 can be self-aligned and is considered to be a new material that can replace doped polysilicon as interconnects.

[0003] Tungsten disilicide (WSi2) has the characteristics of high melting point, good oxidation resistance, and high electrical conductivity, which make it widely used in many fields. Tungsten disilicide has a high melting point and good oxidation resistance. The melting point of WSi2 is as high as 2160℃, and it has good oxidation resistance, which makes it stable in high temperature environment and not easy to be oxidized, which is very suitable for use in high temperature environment. WSi2 has high electrical conductivity, which makes it possible to be used as an inert cathode material for aluminum electrolysis, and its electrical conductivity meets the requirements of cathode materials for aluminum electrolysis. Due to the above characteristics, WSi2 is used in high temperature protective coatings, electronic devices and other fields. For example, in high temperature protective coatings, WSi2 can provide effective anti-oxidation corrosion protection and is widely used in aerospace, energy, petrochemical and other fields. In addition, WSi2 is also studied for use in new two-dimensional materials. WSi2 plays an important role in many fields due to its unique physical and chemical properties. The application field of WSi2 includes the preparation of composite heating elements, among which the composite use of WSi2 and MoSi2 can improve the various properties of heating elements, such as fine microstructure, more uniform distribution, high bending strength and microhardness, and resistivity similar to that of MoSi2 heating elements, while having good thermal stability and high burnout temperature. The valence electron structure analysis of WSi2 shows that the W-Si atomic bonds distributed along the phase in its crystal are the strongest, and the number of covalent electrons and bond energy on these bonds affect the hardness and melting point of the compound. The conductivity and plasticity of WSi2 are relatively poor, which is related to the uneven distribution of its bond network, thus explaining the cause of its brittleness. Due to its unique physical and chemical properties, WSi2 has important application value in high-temperature applications, electronic devices and other fields. WSi2 is often used as an electric shock material in microelectronics, and it is also used as a shunt on polysilicon lines to increase the conductivity and signal speed of polysilicon lines. Tungsten disilicide WSi2 is a compound with special properties. It is a compound composed of two elements, tungsten and silicon, with a very high melting point and hardness. Tungsten disilicide is a material with good electrical conductivity. It has excellent electrical conductivity and thermal stability, so it has broad application prospects in the electronics field. The performance of WSi2 includes its wide application as an ultra-high temperature structural material in the aerospace field, and its application in high-speed cutting tools and other materials that require superhard materials. WSi2 (tungsten disilicide) is an ultra-high temperature structural material with the following main performance characteristics: high temperature stability. WSi2 exhibits good stability at high temperatures and can withstand extreme high temperature environments. It has high hardness. Due to its superhard properties, WSi2 is widely used in the manufacture of high-speed cutting tools and other occasions that require superhard materials. Application fields: WSi2 has attracted widespread attention in the aerospace field and is used to manufacture high-speed cutting tools and other materials that require superhard materials, demonstrating its importance in industrial applications.WSi2 has demonstrated its superiority as an advanced material with its high temperature stability, high hardness and application in aerospace and high-speed cutting tools. WSi2 intermetallic compounds are widely used in the engineering field due to their high strength, high toughness, high melting point, high hardness and good wear resistance as well as corrosion resistance and high temperature oxidation resistance. Moreover, WSi2 intermetallic compounds have high mechanical properties and can be used as a reinforcing and toughening phase for ceramic materials to improve the mechanical properties and high temperature resistance of ceramic materials.

[0004] WC (tungsten carbide) based cemented carbide has excellent physical and chemical properties, including high hardness, good wear resistance, corrosion resistance, and certain electrical conductivity and thermal conductivity. WC has high hardness and wear resistance. The hardness of pure WC is about 2500-2600HV (Vickers hardness), which makes WC based cemented carbide perform well in various industrial applications. By adding different binders, such as Co-based and Ni-based, the properties of the alloy can be further adjusted to meet different application requirements. For example, the hardness range of WC-Co is 855-2050HV, while the fracture toughness range is 4MPa·m 1 / 2 Up to 25MPa·m 1 / 2, showing its adaptability in different application scenarios. WC-based cemented carbide also has good corrosion resistance, which is crucial for many application environments. By adopting specific additives and improved sintering processes, its corrosion resistance can be further improved, thereby expanding its application areas. WC is a good electrical conductor and has the second largest electrical conductivity, second only to silver. In addition, it is also a good conductor of electricity and heat. This excellent property makes WC-based cemented carbide have broad application prospects in applications requiring good electrical and thermal conductivity. WC-based cemented carbide has a wide range of applications in the industry due to its excellent physical and chemical properties, including but not limited to cutting tools, mining tools, molds and wear-resistant and corrosion-resistant components. These properties make WC-based cemented carbide an ideal choice for many industrial applications. WC (tungsten carbide) is a very hard, wear-resistant and high-temperature resistant alloy carbide. It generally exists in tungsten-containing steel in the form of alloy carbide, and there is also pure WC made by powder metallurgy. Tungsten carbide is a compound composed of tungsten and carbon, with a molecular formula of WC and a molecular weight of 195.85. It is a black hexagonal crystal with metallic luster and hardness similar to that of diamond. It is a good conductor of electricity and heat. Tungsten carbide is mainly used to make cemented carbide, but the particles of WC are different depending on the purpose of the alloy. Ultrafine particles of WC are used for finishing alloys; medium particles of WC are used for roughing alloys; medium and coarse particles of WC are used for gravity cutting and heavy cutting alloys; when its wear resistance, pressure resistance and surface finish are emphasized, ultrafine sub-fine particles of WC are used. In addition to being used to produce cemented carbide, WC can also be used as an additive for aerospace cables. WC is a cemented carbide material. Cemented carbide is a composite material composed of multiple metal elements, and its components mainly include tungsten carbide, cobalt and other additives. This material is famous for its high hardness, good wear resistance and heat resistance, and is widely used in the manufacturing of cutting tools, drilling tools, knives, etc. Among them, tungsten carbide provides high hardness of cemented carbide, while cobalt acts as a binder, giving the material better toughness and impact resistance. The preparation process of WC cemented carbide material is quite complicated and needs to be achieved by powder metallurgy. The material maintains its mechanical properties at high temperatures, making it an indispensable material in many industrial applications. Due to its excellent performance, WC cemented carbide has been widely used in manufacturing, mechanical processing, mining and other fields. In addition, WC cemented carbide material also has good processing properties and can be precisely processed by various processing methods to meet the needs of different applications. Therefore, its use in the manufacturing industry is very common and is an indispensable and important material in modern industry.

[0005] W5Si3 intermetallic compounds have high strength, high toughness, high melting point, high hardness, good wear resistance, corrosion resistance and high temperature oxidation resistance, and are widely used in the engineering field. Moreover, W5Si3 intermetallic compounds have high mechanical properties and can be used as reinforcing and toughening phases of ceramic materials to improve the mechanical properties, wear resistance and high temperature oxidation resistance of ceramic materials. WSi2 intermetallic compounds have high strength, high toughness, high melting point, high hardness, good wear resistance, corrosion resistance and high temperature oxidation resistance, and are widely used in the engineering field. Moreover, WSi2 intermetallic compounds have high mechanical properties and can be used as reinforcing and toughening phases of ceramic materials to improve the mechanical properties, wear resistance and high temperature oxidation resistance of ceramic materials. Tungsten carbide ceramic materials have high strength and high hardness, good wear resistance and high temperature oxidation resistance, and are widely used in the engineering field. However, tungsten carbide ceramics are more brittle and have lower fracture toughness, so it is necessary to add reinforcing and toughening phases to the WC matrix. Both W5Si3 intermetallic compounds and WSi2 intermetallic compounds have high flexural strength and high fracture toughness, and can be used as reinforcing and toughening phases of WC ceramics. W5Si3 intermetallic compounds and WSi2 intermetallic compounds have good compatibility with WC. W5Si3 intermetallic compounds and WSi2 intermetallic compounds can be added to the WC matrix to form W5Si3-WSi2 / WC composite materials through compounding, which will greatly improve and enhance the mechanical properties of WC ceramic materials. W5Si3-WSi2 / WC composite materials have high strength, high toughness, high hardness and high wear resistance of W5Si3 intermetallic compounds and WSi2 intermetallic compounds, and also have high hardness and high wear resistance of WC ceramics. W5Si3-WSi2 / WC composite materials will have excellent performance. W5Si3-WSi2 / WC composite materials have high mechanical properties, high hardness and wear resistance, high high temperature oxidation resistance and corrosion resistance. Therefore, the preparation of W5Si3-WSi2 / WC composite materials has become the main research focus and hotspot. For the preparation process of intermetallic compound / ceramic matrix composite materials, some researchers use liquid metal infiltration method to prepare intermetallic compound / ceramic matrix composite materials. Since W5Si3 intermetallic compound has a high melting point of 2320℃, and WSi2 intermetallic compound has a high melting point of 2160℃, it needs to be at a very high temperature to form a liquid phase, which is difficult to form a liquid phase. In addition, W5Si3 intermetallic compound and WSi2 intermetallic compound have poor wettability with WC ceramics, and W5Si3 intermetallic compound and WSi2 intermetallic compound are difficult to penetrate into WC ceramic preforms, so it is impossible to use liquid metal infiltration method to prepare W5Si3-WSi2 / WC composite materials.Therefore, for W5Si3-WSi2 / WC composite materials, only powder metallurgy process can be used for preparation. Powder metallurgy process mainly includes pressureless sintering process, hot pressing sintering process, spark plasma sintering process, and hot isostatic pressing sintering process. Pressureless sintering process, that is, pressureless sintering process, cannot produce dense W5Si3-WSi2 / WC composite materials because there is no pressure for sintering. In the end, only sintered blocks with extremely high porosity are obtained. Therefore, pressureless sintering process cannot be used. Although hot pressing sintering process can produce dense W5Si3-WSi2 / WC composite materials, the preparation process of hot pressing sintering process is very complicated, the sintering time is relatively long, the sintered sample cannot reach complete density, the sintering cost is high, and the price of hot pressing sintering equipment is very expensive, so hot pressing sintering process cannot be used. Hot isostatic pressing sintering process requires hot isostatic press, the price of hot isostatic press equipment is very expensive, the sintering cost is too high, and the preparation process is very complicated, so hot isostatic pressing sintering process cannot be used. Therefore, the only option is to use the spark plasma sintering process with low preparation cost and high sintering efficiency. The spark plasma sintering process has the advantages of fast sintering speed, high density of sintered products, and can achieve mass production. The spark plasma sintering process uses the discharge of electrodes at both ends to generate high-temperature plasma heating to heat the raw material powder in the mold, and applies axial pressure to the raw material powder in the mold, and keeps the temperature and pressure for a certain period of time to obtain a dense sintered product. In order to achieve rapid molding and sintering of composite materials, the present invention proposes to use the spark plasma sintering process to prepare W5Si3-WSi2 / WC composite materials.

[0006] The spark plasma sintering process is a new type of powder metallurgy sintering technology that puts metal powders into a mold made of graphite and other materials, uses upper and lower die punches and powered electrodes to apply specific sintering power and pressing pressure to the sintered powder, and completes the preparation of high-performance materials through discharge activation, thermoplastic deformation and cooling. Spark plasma sintering has the characteristics of sintering during the pressurization process. The plasma generated by the pulse current and the pressurization during the sintering process are conducive to reducing the sintering temperature of the powder. At the same time, the characteristics of low voltage and high current can make the powder sinter quickly and densely. Spark plasma sintering is a new technology for preparing functional materials. It has the characteristics of fast heating speed, short sintering time, and controllable organizational structure. It can be used to prepare metal materials, composite materials, nano-bulk materials, gradient materials, etc. The spark plasma sintering process is a pressure sintering method that uses on-off DC pulse current to directly energize and sinter. The main function of the on-off DC pulse current is to generate discharge plasma, discharge impact pressure, Joule heat and electric field diffusion. During the spark plasma sintering process, the discharge plasma generated instantly when the DC pulse current is passed through the electrode causes each particle inside the sintered body to evenly generate Joule heat and activate the particle surface. Spark plasma sintering is the effective use of the self-heating effect inside the powder for sintering. The spark plasma sintering process can be regarded as the result of the combined effect of particle discharge, conductive heating and pressurization. In the spark plasma sintering technology, the effective discharge between particles can generate local high temperature, which can melt the surface material locally. The spark plasma sintering process has obvious advantages: uniform heating, fast heating rate, low sintering temperature, short sintering time, high production efficiency, fine and uniform product structure, high-density materials can be obtained, and gradient materials and complex workpieces can be sintered. The spark plasma sintering technology device is simple to operate, but it requires a spark plasma sintering furnace. The preparation of new materials using the spark plasma sintering process is mainly concentrated in metal ceramics, intermetallic compounds, composite materials and functional materials. Among them, functional materials include thermoelectric materials, functional gradient materials, etc. The spark plasma sintering process can prepare composite materials, etc. Summary of the invention

[0007] In order to overcome the deficiencies of the above-mentioned prior art, the purpose of the present invention is to provide a W5Si3-WSi2 / WC composite material and a spark plasma sintering preparation method thereof, so as to overcome the problems that the traditional liquid metal infiltration process is too complicated in operation, the preparation cost is high, and the shape and size of the prepared product are limited. At the same time, it also overcomes the difficulties in preparing a W5Si3-WSi2 / WC composite material with high density by using a normal pressure sintering process, and overcomes the shortcomings of a long preparation cycle, high preparation cost, and low sintering process efficiency by using a hot pressing sintering process, and overcomes the shortcomings of a complex hot isostatic pressing sintering process, high preparation cost, and very expensive hot isostatic pressing machine; the spark plasma sintering process can simplify the production process, reduce the production cost, and can also be made into sintered products with complex shapes, and the prepared W5Si3-WSi2 / WC composite material has a high density and high mechanical properties. Since the spark plasma sintering process is carried out at a relatively high sintering temperature and a relatively high hot pressing pressure, and the sintering time of the spark plasma sintering process is relatively short, the grains do not have time to grow before the sintering process ends, so the grains inside the sintered block remain small, the sintered product has a uniform and dense microstructure, the sintered product has high mechanical properties, and the prepared W5Si3-WSi2 / WC composite material block has high mechanical properties and a uniform and dense microstructure. The present invention proposes to prepare a composite material by using a spark plasma sintering process, realize rapid prototyping and sintering of the composite material, have high sintering efficiency and fast sintering speed, and the sintered product has extremely high mechanical properties and extremely high density.

[0008] To achieve the above object, the technical solution adopted by the present invention is:

[0009] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0010] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as reinforcing and toughening phases, and the reinforcing and toughening phases account for 10 to 70 parts; WC is used as a matrix, and the matrix accounts for 30 to 90 parts; Al2O3 powder accounts for 3 to 9 parts; Y2O3 powder accounts for 1 to 7 parts; wherein the Al2O3 powder and the Y2O3 powder are used as sintering aids; and the phenolic resin binder accounts for 9 to 10 parts;

[0011] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound in the strengthening and toughening phase is 1:1.

[0012] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0013] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The W-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 33:67; the prepared W-Si intermetallic compound powder A and W-Si intermetallic compound powder B are subjected to heat treatment process respectively, the heat treatment temperature is 1000℃~1400℃, the heat preservation time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0014] The spark plasma sintering preparation method of the W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0015] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0016] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0017] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0018] The W-Si intermetallic compound powder A and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry. The slurry is placed in a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder A. The mixed powder A is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine. The pressure molding machine is used to press the strip sample at a pressure of 100MPa to 200MPa for a holding time of 3 minutes. The size of the strip sample is 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a temperature of 1000°C to 1400°C for 1 hour. The vacuum degree is 10 -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound powder strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0019] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0020] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0021] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0022] The W-Si intermetallic compound powder B and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to obtain a slurry, the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder B, the mixed powder B is placed in a steel mold for preparing a strip sample, the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is used to press the strip sample at a pressure of 100MPa to 200MPa for a holding time of 3min, and the strip sample has a size of 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a temperature of 1000°C to 1400°C, a holding time of 1h, and a vacuum degree of 10 -2 Pa under vacuum conditions to obtain a WSi2 intermetallic compound powder strip sample with a porous structure, and the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain a WSi2 intermetallic compound powder; in the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0023] Step 5: 10 to 70 parts of the total amount of the W5Si3 intermetallic compound powder A and the WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 30 to 90 parts of WC powder to obtain a mixed powder, 3 to 9 parts of Al2O3 powder and 1 to 7 parts of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a sintered powder composed of W5Si3 powder, WSi2 powder, WC powder, and Al2O3 powder and Y2O3 powder as sintering aids. Mixed powder C; put the mixed powder C into a ball mill, add 100-400 ml of anhydrous ethanol and 30-60 agate grinding balls with a diameter of 10-16 mm into the ball mill for mechanical ball milling, and mix for 24 hours to prepare a slurry; put the slurry into a glass beaker, and put the glass beaker into an oven and dry it at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass ratio of the W5Si3 intermetallic compound powder to the WSi2 intermetallic compound powder is 1:1;

[0024] Step 6: The W5Si3-WSi2 / WC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to prepare slurry, and the slurry is put into a glass beaker and the glass beaker is placed in an oven and dried at 100° C. for 24 hours to obtain mixed powder E containing phenolic resin binder, and the mixed powder E is put into a steel mold capable of making a disc sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is used for 10 The pressure is maintained at 0MPa to 200MPa for 3min, and a disc sample with a diameter of 30mm and a height of about 10mm is pressed. The pressed disc sample is put into a latex glove, wrapped and sealed with the latex glove, and then put into a cold isostatic press. The medium in the cold isostatic press is hydraulic oil. The pressure of the cold isostatic press is 100MPa to 200MPa, and the pressure is maintained for 5min. After the pressure is maintained, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30mm and a height of about 8mm.

[0025] Step 7, placing the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then placing the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering;

[0026] The vacuum spark plasma sintering process is as follows: the sintering temperature is 1500℃~1800℃, the hot pressing pressure is 35MPa, the holding time is 10min, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min, and the furnace is cooled after the sintering process to prepare the W5Si3-WSi2 / WC composite material. The sintered disc sample with a diameter of 30mm and a height of about 6mm is obtained by the spark plasma sintering process, that is, the W5Si3-WSi2 / WC composite material sintered block is obtained, in which a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0027] In the step 5, the particle size of the WC powder is 5 to 8 μm; the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder serve as the reinforcing and toughening phases of the WC matrix, and the mass ratio of the W5Si3 intermetallic compound powder to the WSi2 intermetallic compound powder is 1:1.

[0028] In the step seven, during spark plasma sintering, W5Si3 intermetallic compound particles, WSi2 intermetallic compound particles and WC particles form a dense W5Si3-WSi2 / WC composite material sintered block. W5Si3 particles, WSi2 particles and WC particles have good wettability. During the spark plasma sintering process, W5Si3 particles, WSi2 particles and WC particles can be well bonded together to form a dense sintered block under the conditions of a sintering temperature of 1500°C to 1800°C, a hot pressing pressure of 35MPa and a holding time of 10min; the higher the content of W5Si3 intermetallic compound and WSi2 intermetallic compound, the denser the W5Si3-WSi2 / WC composite material. The role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12 , that is, YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, and improves the mechanical properties of the ceramic composite. The prepared W5Si3-WSi2 / WC composite block has a high density. Since the spark plasma sintering process is carried out at a high sintering temperature and a high hot pressing pressure, and the sintering time of the spark plasma sintering process is relatively short, the sintering process ends before the grains have time to grow, so the grains inside the sintered block remain small, the sintered product has a uniform and dense microstructure, and the sintered product has high mechanical properties. The prepared W5Si3-WSi2 / WC composite block has high mechanical properties and a uniform and dense microstructure.

[0029] The beneficial effects of the present invention are:

[0030] The traditional liquid metal melt infiltration process has high cost, complicated preparation process, limited shape and size of the prepared product, and is difficult to achieve large-scale production and industrialization. The present invention adopts the spark plasma sintering process to prepare W5Si3-WSi2 / WC composite material block. It is impossible to prepare W5Si3-WSi2 / WC composite material by liquid metal infiltration method. The powder metallurgy process used for W5Si3-WSi2 / WC composite material mainly includes normal pressure sintering process, hot pressing sintering process, spark plasma sintering process, and hot isostatic pressing sintering process. Normal pressure sintering process, that is, pressureless sintering process, cannot prepare dense W5Si3-WSi2 / WC composite material because there is no pressure for sintering. What is finally obtained is only a sintered block with extremely high porosity, so normal pressure sintering process cannot be used. Although the hot pressing sintering process can produce dense W5Si3-WSi2 / WC composite materials, the hot pressing sintering process is very complicated, the sintering time is relatively long, the sintered sample cannot be completely dense, the sintering cost is high, and the price of hot pressing sintering equipment is very expensive, so the hot pressing sintering process cannot be used. The hot isostatic pressing sintering process requires a hot isostatic press, the price of the hot isostatic press equipment is very expensive, the sintering cost is too high, and the preparation process is very complicated, so the hot isostatic pressing sintering process cannot be used. Therefore, the only option is to use the spark plasma sintering process with low preparation cost and high sintering efficiency. The spark plasma sintering process has the advantages of fast sintering speed, high density of sintered products, and can achieve mass production. The spark plasma sintering process uses the discharge of electrodes at both ends to generate high-temperature plasma heating to heat the raw material powder in the mold, and applies axial pressure to the raw material powder in the mold, and keeps the heat and pressure for a certain period of time to obtain a dense sintered product. In order to realize the rapid prototyping and sintering of composite materials, the present invention proposes to prepare W5Si3-WSi2 / WC composite materials by using spark plasma sintering process.

[0031] The present invention adopts a spark plasma sintering process to prepare W5Si3-WSi2 / WC composite material bulk. The spark plasma sintering process has low preparation cost and simple preparation process, can realize rapid prototyping and sintering to make composite material products, is suitable for industrial production, and is conducive to industrialization. Therefore, the present invention proposes to adopt a spark plasma sintering process to prepare W5Si3-WSi2 / WC composite material bulk. A mechanical alloying process and a heat treatment process are adopted to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder, and the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder are mixed with WC powder and 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids are added to prepare W5Si3-WSi2 / WC composite powder by wet ball milling, mixing and drying, and the prepared W5Si3-WSi2 / WC composite powder is loaded into a graphite mold, and a W5Si3-WSi2 / WC composite material bulk is prepared by a spark plasma sintering process. The method adopted by the present invention is to utilize the rapid prototyping advantage of the spark plasma sintering process, so that W5Si3 intermetallic compound particles, WSi2 intermetallic compound particles and WC particles can be sintered into a dense W5Si3-WSi2 / WC composite material block under the action of heating and pressure sintering.

[0032] The present invention adopts a spark plasma sintering process with low preparation cost and high sintering efficiency. The spark plasma sintering process can realize rapid molding, low sintering cost, simple preparation process, can produce sintered products with complex shapes, easy industrial production, and conducive to industrialization. The spark plasma sintering process is to heat the raw material powder by generating high-temperature plasma heating through discharge, and at the same time, axial pressure is applied to the raw material powder and the heat preservation and pressure are maintained for a certain time to realize the molding of sintered products. At the same time, in the sintering process of W5Si3-WSi2 / WC composite material, the spark plasma sintering temperature is 1500℃~1800℃, the hot pressing pressure is 35MPa, the insulation time is 10min, and the W5Si3 alloy particles and WSi2 alloy particles are bonded together with the WC particles to form a dense sintered block. The role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12, that is, YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, plays a role in filling pores, and improves the mechanical properties of the ceramic composite. The spark plasma sintering process can obtain a sintered product with a high density and a uniform and dense microstructure, and the sintered product also has high mechanical properties. The W5Si3-WSi2 / WC composite material prepared by the spark plasma sintering process has high mechanical properties, good wear resistance, high temperature oxidation resistance and other excellent properties. Therefore, the W5Si3-WSi2 / WC composite material block prepared by the spark plasma sintering process of the present invention has the advantages of low cost and high performance, can realize rapid prototyping, and can also prepare parts with complex shapes according to engineering needs, so the present invention has important significance and practical value. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The present invention discloses an X-ray diffraction spectrum of a W5Si3-WSi2 / WC composite material block prepared by a spark plasma sintering process according to the method provided by the present invention. DETAILED DESCRIPTION

[0034] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0035] Example 1

[0036] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0037] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0038] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder is prepared; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0039] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0040] The W-Si intermetallic compound powder A and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 100 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1000°C and a holding time of 1 hour. -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0041] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0042] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0043] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0044] The W-Si intermetallic compound powder B and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 100 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1000°C and a holding time of 1 hour. -2 A heat treatment process is carried out under a vacuum condition of Pa, and a WSi2 intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process. After the heat treatment process, the WSi2 intermetallic compound strip sample is taken out, crushed and ground into WSi2 intermetallic compound powder; WSi2 intermetallic compound powder is prepared through the heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0045] Step 5: 10 parts of the W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 90 parts of WC powder to obtain a mixed powder, 3 parts of Al2O3 powder and 7 parts of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; the mixed powder C is put into a ball mill, and 100 ml of Anhydrous ethanol and 30 agate grinding balls with a diameter of 10 mm are mechanically ball-milled for 24 hours to prepare a slurry; the slurry is put into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder is 10 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder is 5 parts and the mass fraction of the WSi2 intermetallic compound powder is 5 parts;

[0046] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, mechanically ball mill and mix for 24 hours to prepare slurry, and put the slurry into a glass beaker, and put the glass beaker into an oven and dry it at 100°C for 24 hours to obtain mixed powder E containing phenolic resin binder, and put the mixed powder E into a steel mold capable of making disc samples, and place the steel mold containing the powder into a pressure molding machine, and A pressure forming machine is used to press a disc sample with a diameter of 30 mm and a height of about 10 mm under a pressure of 100 MPa for a holding time of 3 minutes, the disc sample is put into a latex glove, wrapped and sealed with the latex glove, and then put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure of the cold isostatic press is 100 MPa, and the holding time is 5 minutes. After the holding time is completed, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 8 mm;

[0047] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1500°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained; the mass fraction of the W5Si3 intermetallic compound and the WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 10 parts; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0048] In the steps one and three, the average particle size of the W-Si intermetallic compound powder prepared by ball milling for 80 hours using a mechanical alloying process is 10 to 15 μm, and the powder particle size is extremely fine. The particle size of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder obtained after the heat treatment process is still 10 to 15 μm, and the obtained powders are W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder with an ordered structure.

[0049] In the step 5, the particle size of the WC powder is 5 to 8 μm; the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder serve as the reinforcing and toughening phases of the WC matrix, and the mass ratio of the W5Si3 intermetallic compound powder to the WSi2 intermetallic compound powder is 1:1.

[0050] Example 2

[0051] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0052] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0053] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, and the molar ratio of the W powder to the Si powder is 63:37. After fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 75-80μm; the purity of the Si powder is 99%, and the particle size is 75-81μm;

[0054] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0055] The W-Si intermetallic compound powder A and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 120 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1100°C and a holding time of 1 hour. -2A heat treatment process is carried out under a vacuum condition of 1000 Pa, and a W5Si3 intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process. After the heat treatment process, the W5Si3 intermetallic compound strip sample is taken out, crushed and ground to obtain W5Si3 intermetallic compound powder; W5Si3 intermetallic compound powder is prepared through the heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0056] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0057] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 78-90μm; the purity of the Si powder is 99%, and the particle size is 76-99μm;

[0058] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0059] The W-Si intermetallic compound powder B and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 120 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1100°C and a holding time of 1 hour. -2Pa under vacuum conditions, a heat treatment process is carried out to obtain a porous and loose WSi2 intermetallic compound powder strip sample. After the heat treatment process, the WSi2 intermetallic compound strip sample is taken out and then crushed and ground into WSi2 intermetallic compound powder. WSi2 intermetallic compound powder is prepared by heat treatment process; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0060] Step 5: Mix 20 parts of the W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in Steps 2 and 4 with 80 parts of WC powder to obtain a mixed powder, add 4 parts of Al2O3 powder and 6 parts of Y2O3 powder as sintering aids to the mixed powder, mix the above powders to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; perform a wet ball milling mixing process on the mixed powder C by mechanical ball milling, put the mixed powder C into a ball mill jar, and grind it in a ball mill. Add 150 ml of anhydrous ethanol and 35 agate grinding balls with a diameter of 11 mm into a grinding pot and perform mechanical ball milling for 24 hours to prepare a slurry; put the slurry into a glass beaker and put the glass beaker into an oven and dry it at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder is 20 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder is 10 parts and the mass fraction of the WSi2 intermetallic compound powder is 10 parts;

[0061] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm and mix them by mechanical ball milling for 24 hours to prepare slurry, and then put the slurry into a glass beaker, and then put the glass beaker into an oven and dry it at 100°C for 24 hours to prepare mixed powder E containing phenolic resin binder, and put the mixed powder E into a steel mold capable of making disc samples, and place the steel mold containing the powder into a pressure molding machine, and A pressure forming machine is used to press a disc sample with a diameter of 30 mm and a height of about 10 mm under a pressure of 120 MPa for a holding time of 3 minutes, the disc sample is put into a latex glove, wrapped and sealed with the latex glove, and then put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure of the cold isostatic press is 120 MPa, the holding time is 5 minutes, the sample is taken out after the holding time is completed, and a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 8 mm is formed by isostatic pressing on the cold isostatic press;

[0062] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1550°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained. The mass fraction of W5Si3 intermetallic compound and WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 20 parts; a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0063] Example 3

[0064] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0065] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0066] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 90-100μm; the purity of the Si powder is 99%, and the particle size is 89-100μm;

[0067] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0068] The W-Si intermetallic compound powder A and 10 parts by mass of a phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry, and the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold that can be used to make strip samples, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is used to press the strip samples at a pressure of 140 MPa for a holding time of 3 minutes, and the size of the strip samples is 50 mm×5 mm×6 mm, and the strip samples are placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace, wherein the heat treatment temperature is 1200°C, the holding time is 1 hour, and the vacuum degree is 10 -2 A heat treatment process is carried out under a vacuum condition of 1000 Pa, and a W5Si3 intermetallic compound powder strip sample with a porous structure is obtained through the heat treatment process. After the heat treatment process is completed, the W5Si3 intermetallic compound strip sample is taken out, and then crushed and ground to obtain W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0069] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0070] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, and the grinding balls are agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 90-100μm; the purity of the Si powder is 99%, and the particle size is 89-100μm;

[0071] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0072] The W-Si intermetallic compound powder B and 10 parts by mass of phenolic resin binder are loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 140 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is loaded into a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1200°C and a holding time of 1 hour. -2 Pa under vacuum conditions, a heat treatment process is performed to obtain a porous and loose WSi2 intermetallic compound powder strip sample. After the heat treatment process, the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain WSi2 intermetallic compound powder. In the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0073] Step 5: Mix 30 parts of the W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in Steps 2 and 4 with 70 parts of WC powder to obtain a mixed powder, add 5 parts of Al2O3 powder and 5 parts of Y2O3 powder as sintering aids to the mixed powder, mix the above powders to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; put the mixed powder C into a ball mill, add 200 ml of anhydrous Ethanol and 40 agate grinding balls with a diameter of 12 mm are mechanically ball-milled for 24 hours to prepare a slurry; the slurry is put into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder is 30 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder is 15 parts and the mass fraction of the WSi2 intermetallic compound powder is 15 parts;

[0074] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, mix by mechanical ball milling for 24 hours to prepare slurry, mix by wet ball milling to prepare slurry and put the slurry into a glass beaker, and put the glass beaker into an oven at 100°C and dry for 24 hours to obtain mixed powder E containing phenolic resin binder, and put the mixed powder E containing a small amount of phenolic resin binder into a steel mold capable of making a disc sample, and put the steel mold filled with powder into the steel mold. The sample was placed in a pressure forming machine, and the pressure was maintained at 140 MPa for 3 minutes to form a disc sample with a diameter of 30 mm and a height of about 10 mm. The disc sample was placed in a latex glove, wrapped and sealed with the latex glove, and then placed in a cold isostatic press. The medium in the cold isostatic press was hydraulic oil. The pressure of the cold isostatic press was 140 MPa, and the pressure was maintained for 5 minutes. After the pressure was maintained, the sample was taken out and isostatically pressed by the cold isostatic press to form a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 8 mm.

[0075] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1600°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10-2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained. The mass fraction of W5Si3 intermetallic compound and WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 30 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0076] Example 4

[0077] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0078] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0079] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 95-100μm; the purity of the Si powder is 99%, and the particle size is 96-100μm;

[0080] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0081] The W-Si intermetallic compound powder A and 10 parts by mass of phenolic resin binder are loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which is mixed by wet ball milling to prepare a slurry and loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 150 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1250°C and a holding time of 1 hour. -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound powder strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0082] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0083] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 95-100μm; the purity of the Si powder is 99%, and the particle size is 96-100μm;

[0084] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0085] The W-Si intermetallic compound powder B and 10 parts by mass of phenolic resin binder are loaded into a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which is then mixed by wet ball milling to prepare a slurry, and the slurry is loaded into a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed into a strip sample at a pressure of 150 MPa for a holding time of 3 minutes, and the size of the strip sample is 50 mm×5 mm×6 mm, and the strip sample is loaded into a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1250°C and a holding time of 1 hour. -2 Pa under vacuum conditions to obtain a WSi2 intermetallic compound powder strip sample with a porous structure, and the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain a WSi2 intermetallic compound powder; in the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0086] Step 5, 40 parts of the total amount of W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 60 parts of WC powder to obtain a mixed powder, 6 parts of Al2O3 powder and 4 parts of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; the mixed powder C is subjected to a wet ball milling mixing process by mechanical ball milling, and the mixed powder C is loaded into a ball mill jar, and the ball mill jar is heated to 30 ℃ and 80 ℃. 250 ml of anhydrous ethanol and 45 agate grinding balls with a diameter of 13 mm were added to the mixture for mechanical ball milling, and the mixture was mixed for 24 hours to prepare a slurry; the slurry was put into a glass beaker, and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder was 40 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder was 20 parts and the mass fraction of the WSi2 intermetallic compound powder was 20 parts;

[0087] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to prepare a slurry, mix them by wet ball milling to prepare a slurry, and put the glass beaker into an oven and dry it at 100°C for 24 hours to obtain a mixed powder E containing a phenolic resin binder, and put the mixed powder E containing a small amount of phenolic resin binder into a steel mold capable of making a disc sample, and place the steel mold filled with the powder into a pressure forming machine. The W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample has a diameter of 30 mm and a height of about 8 mm.

[0088] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1650°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained. The mass fraction of W5Si3 intermetallic compound and WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 40 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0089] Example 5

[0090] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0091] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0092] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0093] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0094] The W-Si intermetallic compound powder A and 10 parts by mass of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, which was placed in a steel mold for preparing a strip sample, and the steel mold containing the powder was placed in a pressure molding machine, and the pressure molding machine was pressed into a strip sample at a pressure of 160 MPa for a holding time of 3 minutes, and the size of the strip sample was 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and the graphite crucible was placed in a vacuum sintering furnace for heat treatment at a temperature of 1300°C and a holding time of 1 hour. -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound powder strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0095] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0096] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0097] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0098] The W-Si intermetallic compound powder and 10 parts by mass of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added, and the mixture was mixed by mechanical ball milling for 24 hours to prepare a slurry, and the slurry was mixed by wet ball milling, and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder, and the mixed powder was placed in a steel mold capable of making strip samples, and the steel mold containing the powder was placed in a pressure molding machine, and the pressure molding machine was used to press the strip samples at a pressure of 160 MPa for a holding time of 3 minutes, and the size of the strip samples was 50 mm×5 mm×6 mm, and the strip samples were placed in a graphite crucible, and the graphite crucible was placed in a vacuum sintering furnace, wherein the heat treatment temperature was 1300°C, the holding time was 1 hour, and the vacuum degree was 10 -2 Pa under vacuum conditions to obtain a WSi2 intermetallic compound powder strip sample with a porous structure, and the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain a WSi2 intermetallic compound powder; in the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0099] Step 5, 50 parts of the total amount of W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 50 parts of WC powder to obtain a mixed powder, 7 parts of Al2O3 powder and 3 parts of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; the mixed powder C is subjected to a wet ball milling mixing process by mechanical ball milling, and the mixed powder C is loaded into a ball mill jar, and the ball mill jar is heated to 30 ℃ and 80 ℃. 300 ml of anhydrous ethanol and 50 agate grinding balls with a diameter of 14 mm were added to the mixture for mechanical ball milling, and the mixture was mixed for 24 hours to prepare a slurry; the slurry was put into a glass beaker, and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder was 50 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder was 25 parts and the mass fraction of the WSi2 intermetallic compound powder was 25 parts;

[0100] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to prepare a slurry, mix them by wet ball milling to prepare a slurry, and put the glass beaker into an oven and dry it at 100°C for 24 hours to obtain a mixed powder E containing a phenolic resin binder, and put the mixed powder E containing a small amount of phenolic resin binder into a steel mold capable of making a disc sample, and place the steel mold filled with the powder into a pressure forming machine. The W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and is formed into a W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 10 mm by a pressure forming machine at a pressure of 160 MPa for a holding time of 3 minutes. The disc sample is put into a latex glove, wrapped and sealed with the latex glove, and then put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure of the cold isostatic press is 160 MPa, and the holding time is 5 minutes. After the holding time is completed, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 8 mm.

[0101] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1700°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained. The mass fraction of the W5Si3 intermetallic compound and the WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 50 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0102] Example 6

[0103] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0104] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0105] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 80-90μm; the purity of the Si powder is 99%, and the particle size is 79-91μm;

[0106] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0107] The W-Si intermetallic compound powder A and 10 parts by mass of phenolic resin binder were placed in a ball mill, and 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, which was placed in a steel mold for preparing a strip sample, and the steel mold containing the powder was placed in a pressure molding machine, and the pressure molding machine was pressed at a pressure of 180 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and the graphite crucible was placed in a vacuum sintering furnace for heat treatment at a temperature of 1350°C and a holding time of 1 hour. -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound powder strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0108] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0109] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 80-90μm; the purity of the Si powder is 99%, and the particle size is 79-91μm;

[0110] Step 4: subjecting the W-Si intermetallic compound powder prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0111] The W-Si intermetallic compound powder B and 10 parts by mass of phenolic resin binder were placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, and the mixed powder B was placed in a steel mold for preparing strip samples, and the steel mold containing the powder was placed in a pressure molding machine, and the pressure molding machine was pressed into a strip sample at a pressure of 180 MPa for a holding time of 3 minutes, and the size of the strip sample was 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and then the graphite crucible was placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1350°C and a holding time of 1 hour. -2 Pa under vacuum conditions to obtain a WSi2 intermetallic compound powder strip sample with a porous structure, and the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain a WSi2 intermetallic compound powder; in the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0112] Step 5, a total of 60 parts of the W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 40 parts of WC powder to obtain a mixed powder, 8 parts of Al2O3 powder and 2 parts of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; the mixed powder C is subjected to a wet ball milling mixing process by mechanical ball milling, and the mixed powder C is loaded into a ball mill jar, and the ball mill jar is heated to 30 ℃ and 80 ℃. 350 ml of anhydrous ethanol and 55 agate grinding balls with a diameter of 15 mm were added to the mixture for mechanical ball milling, and the mixture was mixed for 24 hours to prepare a slurry; the slurry was put into a glass beaker, and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder was 60 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder was 30 parts and the mass fraction of the WSi2 intermetallic compound powder was 30 parts;

[0113] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to prepare a slurry, mix them by wet ball milling to prepare a slurry, and put the glass beaker into an oven and dry it at 100°C for 24 hours to obtain a mixed powder E containing a phenolic resin binder, and put the mixed powder E containing a small amount of phenolic resin binder into a steel mold capable of making a disc sample, and place the steel mold filled with the powder into a pressure forming machine. The W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and is formed into a compact W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 10 mm by means of a pressure forming machine at a pressure of 180 MPa for a holding time of 3 minutes, and the disc sample is put into a latex glove, wrapped and sealed with the latex glove, and then put into a cold isostatic press, the medium in the cold isostatic press is hydraulic oil, the pressure of the cold isostatic press is 180 MPa, and the holding time is 5 minutes, and the sample is taken out after the holding time is completed, and isostatically pressed by the cold isostatic press to form a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30 mm and a height of about 8 mm;

[0114] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1750°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained. The mass fraction of W5Si3 intermetallic compound and WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 60 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0115] Embodiment 7:

[0116] The spark plasma sintering preparation method of W5Si3-WSi2 / WC composite material comprises the following steps in parts by weight:

[0117] Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are:

[0118] W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0119] Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is:

[0120] The W-Si intermetallic compound powder A and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which is mixed by wet ball milling to prepare a slurry and the glass beaker is placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder A, and the mixed powder A is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is pressed at a pressure of 200 MPa for a holding time of 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm, and the strip sample is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a heat treatment temperature of 1400°C and a holding time of 1 hour. -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound powder strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0121] Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are:

[0122] The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm;

[0123] Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are:

[0124] The W-Si intermetallic compound powder B and 10 parts by mass of phenolic resin binder were placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm were added and mixed by mechanical ball milling for 24 hours to prepare a slurry, which was mixed by wet ball milling to prepare a slurry and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a mixed powder B, the mixed powder B was placed in a steel mold for preparing strip samples, the steel mold containing the powder was placed in a pressure molding machine, and the pressure molding machine was pressed at a pressure of 200 MPa for 3 minutes to form a strip sample with a size of 50 mm×5 mm×6 mm, and the strip sample was placed in a graphite crucible, and the graphite crucible was placed in a vacuum sintering furnace for heat treatment at a temperature of 1400°C and a holding time of 1 hour. -2 Pa under vacuum conditions to obtain a WSi2 intermetallic compound powder strip sample with a porous structure, and the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain a WSi2 intermetallic compound powder; in the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder;

[0125] Step 5, a total of 70 parts of the W5Si3 intermetallic compound powder A and WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 30 parts of WC powder to obtain a mixed powder, 9 parts of Al2O3 powder and 1 part of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a mixed powder C composed of W5Si3 powder, WSi2 powder, WC powder, Al2O3 powder and Y2O3 powder as sintering aids; the mixed powder C is subjected to a wet ball milling mixing process by mechanical ball milling, and the mixed powder C is loaded into a ball mill jar, and the ball mill jar is heated to 300 ℃. 400 ml of anhydrous ethanol and 60 agate grinding balls with a diameter of 16 mm were added to the mixture for mechanical ball milling, and the mixture was mixed for 24 hours to prepare a slurry; the slurry was put into a glass beaker, and the glass beaker was placed in an oven and dried at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass fraction of the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder in the W5Si3-WSi2 / WC composite powder was 70 parts; wherein the mass fraction of the W5Si3 intermetallic compound powder was 35 parts and the mass fraction of the WSi2 intermetallic compound powder was 35 parts;

[0126] Step 6: Mix the W5Si3-WSi2 / WC composite powder obtained in step 5 with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then add 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm, and mix them by mechanical ball milling for 24 hours to prepare a slurry, mix them by wet ball milling to prepare a slurry, and put the glass beaker into an oven and dry it at 100°C for 24 hours to obtain a mixed powder E containing a phenolic resin binder, and put the mixed powder E containing a small amount of phenolic resin binder into a steel mold capable of making a disc sample, and place the steel mold filled with the powder into a pressure forming machine. The W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample is prepared by isostatic pressing in a cold isostatic press, and the W5Si3-WSi2 / WC composite powder preform body disc sample has a diameter of 30 mm and a height of about 8 mm.

[0127] Step 7: Place the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then place the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering. The vacuum spark plasma sintering process preparation method is as follows: the sintering temperature is 1800°C, the hot pressing pressure is 35MPa, the holding time is 10min, and the spark plasma sintering process is carried out under vacuum conditions, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min; after the sintering process is completed, the furnace is cooled to prepare the W5Si3-WSi2 / WC composite material. Through the spark plasma sintering process, a sintered disc sample with a diameter of 30mm and a height of about 6mm can be obtained, that is, a sintered block of the W5Si3-WSi2 / WC composite material is obtained. The mass fraction of W5Si3 intermetallic compound and WSi2 intermetallic compound in the W5Si3-WSi2 / WC composite material is 70 parts. A small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

[0128] Example 8

[0129] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0130] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 10 parts; WC is used as the matrix, and the matrix accounts for 90 parts; Al2O3 powder accounts for 3 parts; Y2O3 powder accounts for 7 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 9 parts;

[0131] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1.

[0132] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0133] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder B is prepared by ball milling for 80 hours by mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1000°C, the heat preservation time is 1h, and the vacuum degree is 10-2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0134] Example 9

[0135] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0136] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 20 parts; WC is used as the matrix, and the matrix accounts for 80 parts; Al2O3 powder accounts for 4 parts; Y2O3 powder accounts for 6 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0137] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1.

[0138] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0139] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The W-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1100°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0140] Example 10

[0141] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0142] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 30 parts; WC is used as the matrix, and the matrix accounts for 70 parts; Al2O3 powder accounts for 5 parts; Y2O3 powder accounts for 5 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 9 parts;

[0143] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1.

[0144] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0145] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder B is prepared by ball milling for 80 hours by mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1200°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0146] Embodiment 11

[0147] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0148] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 40 parts; WC is used as the matrix, and the matrix accounts for 60 parts; Al2O3 powder accounts for 6 parts; Y2O3 powder accounts for 4 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0149] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1;

[0150] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0151] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The W-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1250°C, the holding time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0152] Example 12

[0153] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0154] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase is 50 parts; WC is used as the matrix, and the matrix is ​​50 parts; Al2O3 powder is 7 parts; Y2O3 powder is 3 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder is 10 parts;

[0155] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1.

[0156] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0157] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder B is prepared by ball milling for 80 hours by mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1300°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0158] Example 13

[0159] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0160] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 60 parts; WC is used as the matrix, and the matrix accounts for 40 parts; Al2O3 powder accounts for 8 parts; Y2O3 powder accounts for 2 parts; Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0161] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1.

[0162] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0163] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The W-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1350°C, the holding time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0164] Embodiment 14

[0165] The W5Si3-WSi2 / WC composite material comprises the following components in parts by weight:

[0166] In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as the strengthening and toughening phase, and the strengthening and toughening phase accounts for 70 parts; WC is used as the matrix, and the matrix accounts for 30 parts; Al2O3 powder accounts for 9 parts; Y2O3 powder accounts for 1 part; wherein Al2O3 powder and Y2O3 powder are used as sintering aids; phenolic resin binder accounts for 10 parts;

[0167] The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound is 1:1.

[0168] The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37;

[0169] The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder B is prepared by ball milling for 80 hours by mechanical alloying process, wherein the molar ratio of W:Si is 33:67; and the prepared W-Si intermetallic compound powder with a molar ratio of W:Si of 63:37 and the W-Si intermetallic compound powder with a molar ratio of W:Si of 33:67 are subjected to heat treatment process respectively, the heat treatment temperature is 1400°C, the heat preservation time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

[0170] It can be seen from Examples 1-7 that the spark plasma sintering process used in Examples 1-7 has a simple preparation process, low cost, high sintering efficiency, and can achieve rapid prototyping. The spark plasma sintering process has a low cost and a simple preparation process, and can also produce a dense composite material block. Therefore, the main advantages of the present invention over existing technologies are:

[0171] 1) The present invention adopts a mechanical alloying process combined with a heat treatment process to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder, and the prepared W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder are mixed with WC powder, and 10 parts by weight of Al2O3 powder and Y2O3 powder sintering aids are added to prepare W5Si3-WSi2 / WC composite powder by wet ball milling and drying, and W5Si3-WSi2 / WC composite material block is prepared by spark plasma sintering process. The purpose of adding 10 parts by weight of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and the Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, and improves the mechanical properties of the ceramic composite. The spark plasma sintering preparation process has low cost, simple preparation process, high sintering efficiency, can achieve rapid molding sintering, and can also prepare W5Si3-WSi2 / WC composite block with uniform and dense organizational structure.

[0172] 2) The W5Si3-WSi2 / WC composite material prepared by the spark plasma sintering process has a uniform and dense microstructure and high mechanical properties, and also has the high melting point, high hardness, high elastic modulus and other properties of the W5Si3 intermetallic compound and the WSi2 intermetallic compound. The W5Si3-WSi2 / WC composite material prepared by the spark plasma sintering process has a high density and a uniform and dense microstructure. The W5Si3-WSi2 / WC composite material prepared by the spark plasma sintering process has high mechanical properties and high hardness, as well as high wear resistance and good high temperature oxidation resistance. The present invention develops a new preparation process for the low-cost manufacture of the W5Si3-WSi2 / WC composite material, and the present invention lays a foundation for popularizing and promoting the wide application of the W5Si3-WSi2 / WC composite material in the engineering field.

[0173] 3) In the preparation process of W5Si3-WSi2 / WC composite material block, the role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12 , namely, YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, and improves the mechanical properties of the ceramic composite. During the heat treatment of the W-Si intermetallic compound powder, 10 parts by mass of phenolic resin binder are added to the W-Si intermetallic compound powder to improve the strength and hardness of the strip sample blank after pressure forming, prevent fracture and damage when taking the sample and putting it in the graphite crucible, and ensure the integrity of the sample. The phenolic resin binder decomposes into gas at high temperature and volatilizes, leaving only a small amount of residual carbon. A small amount of residual carbon is mixed in the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder after the heat treatment process, which will not affect the final product. The purpose of adding 10 parts by mass of phenolic resin binder to the W5Si3-WSi2 / WC composite powder is to improve the strength and hardness of the disc sample preform pressed after pressure forming, prevent the disc sample preform from breaking and being damaged when taking the sample and placing it in the graphite mold, and ensure the integrity of the sample. The phenolic resin binder decomposes into gas at high temperature and evaporates, leaving only a small amount of residual carbon. The small amount of residual carbon is mixed in the sample after spark plasma sintering and will not affect the final product.

[0174] Figure 1 The present invention discloses an X-ray diffraction spectrum of a W5Si3-WSi2 / WC composite material block prepared by a spark plasma sintering process according to the method provided by the present invention. Figure 1The XRD pattern of W5Si3-WSi2 / WC composite material bulk prepared by spark plasma sintering process. Figure 1 It can be seen that in the XRD spectrum, there are diffraction peaks of W5Si3 intermetallic compound phase, WSi2 intermetallic compound phase, and WC ceramic phase. In addition, there is a small amount of Y3Al5O 12 The diffraction peak of the phase is the diffraction peak of the YAG phase. During the sintering process, the Al2O3 powder and the Y2O3 powder sintering aid react at high temperature to form liquid Y3Al5O 12 , namely YAG phase, forming a liquid phase to promote the densification of the ceramic composite matrix and improve the mechanical properties of the ceramic composite. In the XRD spectrum, there are diffraction peaks of the W5Si3 intermetallic compound phase, the WSi2 intermetallic compound phase, and the WC ceramic phase. This shows that in the preparation process of the spark plasma sintering process, the W5Si3 intermetallic compound and the WSi2 intermetallic compound do not react with the WC ceramic to generate other impurity phases, and the W5Si3 intermetallic compound and the WSi2 intermetallic compound have good compatibility with the WC ceramic. Therefore, the W5Si3 intermetallic compound and the WSi2 intermetallic compound can be sintered together with the WC ceramic by the spark plasma sintering process to form a dense W5Si3-WSi2 / WC composite material, in which the W5Si3 intermetallic compound and the WSi2 intermetallic compound are the reinforcing and toughening phases, and the WC ceramic is the matrix. W5Si3 intermetallic compounds and WSi2 intermetallic compounds play a role in strengthening and toughening WC ceramics. W5Si3 intermetallic compounds and WSi2 intermetallic compounds can significantly improve the mechanical properties of WC ceramics. W5Si3-WSi2 / WC composite materials have the excellent properties of W5Si3 intermetallic compounds and WSi2 intermetallic compounds, and also have the excellent properties of WC ceramics. The present invention develops a new preparation process for low-cost manufacturing of W5Si3-WSi2 / WC composite materials. The W5Si3-WSi2 / WC composite materials prepared by the spark plasma sintering process have high preparation efficiency and low preparation cost. The W5Si3-WSi2 / WC composite materials prepared by the spark plasma sintering process have high density and uniform and dense microstructure. The W5Si3-WSi2 / WC composite materials prepared by the spark plasma sintering process have high mechanical properties and high hardness, as well as good wear resistance and good high temperature oxidation resistance. The present invention develops a new preparation process for low-cost manufacturing of W5Si3-WSi2 / WC composite materials, and the present invention lays a foundation for popularizing and promoting the wide application of W5Si3-WSi2 / WC composite materials in the engineering field.

Claims

1. W5Si3-WSi2 / WC composite material, by weight, characterized in that: Includes the following components: In the W5Si3-WSi2 / WC composite material, W5Si3 intermetallic compound and WSi2 intermetallic compound are used as reinforcing and toughening phases, and the reinforcing and toughening phases account for 10 to 70 parts; WC is used as a matrix, and the matrix accounts for 30 to 90 parts; Al2O3 powder accounts for 3 to 9 parts; Y2O3 powder accounts for 1 to 7 parts; wherein the Al2O3 powder and the Y2O3 powder are used as sintering aids; and the phenolic resin binder accounts for 9 to 10 parts; The mass ratio of the W5Si3 intermetallic compound to the WSi2 intermetallic compound in the strengthening and toughening phase is 1:

1.

2. The W5Si3-WSi2 / WC composite material according to claim 1, characterized in that: The W5Si3 intermetallic compound powder is prepared by mechanical alloying and heat treatment process, and the W-Si intermetallic compound powder A is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 63:37; The WSi2 intermetallic compound powder is prepared by mechanical alloying and heat treatment process. The W-Si intermetallic compound powder B is prepared by ball milling for 80 hours using the mechanical alloying process, wherein the molar ratio of W:Si is 33:67; the prepared W-Si intermetallic compound powder A and W-Si intermetallic compound powder B are subjected to heat treatment process respectively, the heat treatment temperature is 1000℃~1400℃, the heat preservation time is 1h, and the vacuum degree is 10 -2 Pa, a heat treatment process was carried out to prepare W5Si3 intermetallic compound powder and WSi2 intermetallic compound powder respectively.

3. The spark plasma sintering preparation method of the W5Si3-WSi2 / WC composite material according to claim 1, characterized in that, by weight, The following steps are involved: Step 1: Preparation of W-Si intermetallic compound powder A, using mechanical alloying and heat treatment process, the specific steps are: W powder and Si powder are loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill is a polytetrafluoroethylene ball mill, the grinding balls are agate grinding balls, the mass ratio of the agate grinding balls to the mixed powder is 10:1, wherein the molar ratio of the W powder to the Si powder is 63:37, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, argon gas is filled into the ball mill as a protective gas, and W-Si intermetallic compound powder A is prepared; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm; Step 2: heat-treating the W-Si intermetallic compound powder A prepared in step 1 to obtain W5Si3 intermetallic compound powder. The specific method is: The W-Si intermetallic compound powder A and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to form a slurry, which is then mixed by wet ball milling to form a slurry. The slurry is placed in a glass beaker and the glass beaker is placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder A. The mixed powder A is placed in a steel mold for preparing a strip sample, and the steel mold containing the powder is placed in a pressure molding machine. The pressure molding machine is used to press the strip sample at a pressure of 100MPa to 200MPa for a holding time of 3 minutes. The size of the strip sample is 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a temperature of 1000°C to 1400°C for 1 hour. The vacuum degree is 10 -2 Pa, a W5Si3 intermetallic compound powder strip sample with a loose porous structure is obtained, the W5Si3 intermetallic compound powder strip sample is taken out, crushed and ground to obtain a W5Si3 intermetallic compound powder; in the prepared W5Si3 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder; Step 3: Preparation of W-Si intermetallic compound powder B by mechanical alloying process. The specific steps are: The W powder and the Si powder are mixed to obtain a mixed powder B, and the mixed powder B is loaded into a ball mill of a QM-1SP2 planetary ball mill, wherein the ball mill adopts a polytetrafluoroethylene ball mill, and the grinding balls adopt agate grinding balls, and the mass ratio of the agate grinding balls to the mixed powder B is 10:1, wherein the molar ratio of the W powder to the Si powder is 33:67, and after fixing four ball mills, the planetary ball mill is started for mechanical ball milling, the mechanical ball milling time is 80 hours, the speed of the ball mill is 400r / min, dry ball milling is adopted, and intermittent ball milling is adopted, and argon gas is filled in the ball mill as a protective gas to prepare W-Si intermetallic compound powder B; the purity of the W powder is 99%, and the particle size is 75-100μm; the purity of the Si powder is 99%, and the particle size is 75-100μm; Step 4: subjecting the W-Si intermetallic compound powder B prepared in step 3 to a heat treatment process to obtain WSi2 intermetallic compound powder. The specific steps are: The W-Si intermetallic compound powder B and 10 parts of phenolic resin binder are placed in a ball mill, and then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added and mixed by mechanical ball milling for 24 hours to obtain a slurry, the slurry is placed in a glass beaker, and the glass beaker is placed in an oven and dried at 100°C for 24 hours to obtain a mixed powder B, the mixed powder B is placed in a steel mold for preparing a strip sample, the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is used to press the strip sample at a pressure of 100MPa to 200MPa for a holding time of 3min, and the strip sample has a size of 50mm×5mm×6mm, and the strip sample is placed in a graphite crucible, and then the graphite crucible is placed in a vacuum sintering furnace for heat treatment at a temperature of 1000°C to 1400°C, a holding time of 1h, and a vacuum degree of 10 -2 Pa under vacuum conditions to obtain a WSi2 intermetallic compound powder strip sample with a porous structure, and the WSi2 intermetallic compound strip sample is taken out, crushed and ground to obtain a WSi2 intermetallic compound powder; in the prepared WSi2 intermetallic compound powder, a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature heat treatment process, and no phenolic resin remains in the obtained powder; Step 5: 10 to 70 parts of the total amount of the W5Si3 intermetallic compound powder A and the WSi2 intermetallic compound powder B prepared in step 2 and step 4 are mixed with 30 to 90 parts of WC powder to obtain a mixed powder, 3 to 9 parts of Al2O3 powder and 1 to 7 parts of Y2O3 powder as sintering aids are added to the mixed powder, and the above powders are mixed to obtain a sintered powder composed of W5Si3 powder, WSi2 powder, WC powder, and Al2O3 powder and Y2O3 powder as sintering aids. Mixed powder C; put the mixed powder C into a ball mill, add 100-400 ml of anhydrous ethanol and 30-60 agate grinding balls with a diameter of 10-16 mm into the ball mill for mechanical ball milling, and mix for 24 hours to prepare a slurry; put the slurry into a glass beaker, and put the glass beaker into an oven and dry it at 100°C for 24 hours to prepare a W5Si3-WSi2 / WC composite powder; wherein the mass ratio of the W5Si3 intermetallic compound powder to the WSi2 intermetallic compound powder is 1:1; Step 6: The W5Si3-WSi2 / WC composite powder obtained in step 5 is mixed with 10 parts of phenolic resin binder to prepare mixed powder D and put it into a ball mill, then 300 ml of anhydrous ethanol and 30 agate grinding balls with a diameter of 15 mm are added, and mechanical ball milling is performed for 24 hours to prepare slurry, and the slurry is put into a glass beaker and the glass beaker is placed in an oven and dried at 100° C. for 24 hours to obtain mixed powder E containing phenolic resin binder, and the mixed powder E is put into a steel mold capable of making a disc sample, and the steel mold containing the powder is placed in a pressure molding machine, and the pressure molding machine is used for 10 The pressure is maintained at 0MPa to 200MPa for 3min, and a disc sample with a diameter of 30mm and a height of about 10mm is pressed. The pressed disc sample is put into a latex glove, wrapped and sealed with the latex glove, and then put into a cold isostatic press. The medium in the cold isostatic press is hydraulic oil. The pressure of the cold isostatic press is 100MPa to 200MPa, and the pressure is maintained for 5min. After the pressure is maintained, the sample is taken out and isostatically pressed by the cold isostatic press to form a dense W5Si3-WSi2 / WC composite powder preform disc sample with a diameter of 30mm and a height of about 8mm. Step 7, placing the W5Si3-WSi2 / WC composite powder preform disc sample obtained in step 6 into a graphite mold, and then placing the graphite mold into a spark plasma sintering furnace for vacuum spark plasma sintering; The vacuum spark plasma sintering process is as follows: the sintering temperature is 1500℃~1800℃, the hot pressing pressure is 35MPa, the holding time is 10min, and the vacuum degree is 10 -2 Pa, the heating rate during the sintering process is 100℃ / min, and the furnace is cooled after the sintering process to prepare the W5Si3-WSi2 / WC composite material. The sintered disc sample with a diameter of 30mm and a height of about 6mm is obtained by the spark plasma sintering process, that is, the W5Si3-WSi2 / WC composite material sintered block is obtained, in which a small amount of phenolic resin is completely decomposed and volatilized during the high-temperature spark plasma sintering process, and there is no residual phenolic resin in the obtained sintered block.

4. The spark plasma sintering preparation method of the W5Si3-WSi2 / WC composite material according to claim 3, characterized in that: In the step 5, the particle size of the WC powder is 5 to 8 μm; the W5Si3 intermetallic compound powder and the WSi2 intermetallic compound powder serve as the reinforcing and toughening phases of the WC matrix, and the mass ratio of the W5Si3 intermetallic compound powder to the WSi2 intermetallic compound powder is 1:

1. In the step seven, during spark plasma sintering, W5Si3 intermetallic compound particles, WSi2 intermetallic compound particles and WC particles form a dense W5Si3-WSi2 / WC composite material sintered block. W5Si3 particles, WSi2 particles and WC particles have good wettability. During the spark plasma sintering process, W5Si3 particles, WSi2 particles and WC particles can be well bonded together to form a dense sintered block under the conditions of a sintering temperature of 1500°C to 1800°C, a hot pressing pressure of 35MPa and a holding time of 10min; the higher the content of W5Si3 intermetallic compound and WSi2 intermetallic compound, the denser the W5Si3-WSi2 / WC composite material. The role of adding 10 parts by mass of Al2O3 powder and Y2O3 powder sintering aids is that during the sintering process, the Al2O3 powder and Y2O3 powder sintering aids react at high temperature to form liquid Y3Al5O 12 , that is, YAG phase, forms a liquid phase to promote the densification of the ceramic composite matrix, fills the pores, and improves the mechanical properties of the ceramic composite. The prepared W5Si3-WSi2 / WC composite block has a high density. Since the spark plasma sintering process is carried out at a high sintering temperature and a high hot pressing pressure, and the sintering time of the spark plasma sintering process is relatively short, the sintering process ends before the grains have time to grow, so the grains inside the sintered block remain small, the sintered product has a uniform and dense microstructure, and the sintered product has high mechanical properties. The prepared W5Si3-WSi2 / WC composite block has high mechanical properties and a uniform and dense microstructure.